Chanel couture and industry - De la Haye, Amy (V & A Publishing, 2023)
"For over a century, the name Chanel has been synonymous with elegance, modernity and innovation. This lavishly illustrated book, newly expanded and updated, examines the creative output of Gabrielle 'Coco' Chanel (1883-1971) over the course of her long career, documenting the meteoric rise of the Chanel fashion empire and its exclusive legacy across haute couture, ready-to-wear, accessories, jewellery and perfumes. The story is brought up to date, looking at the House after Gabrielle Chanel : the vision of creative director Karl Lagerfeld, who from 1983 until his death in 2019 ensured that the brand remained at fashion's vanguard; and the reinterpreting of Chanel fashion signatures by his successor, Virginie Viard, today." -- Back cover
Keywords: Chanel, Coco -- 1883-1971; Chanel -- Firma; Geschichte; Chanel, Coco / 1883-1971 / Exhibitions; Chanel (Firm) / History / Exhibitions; Fashion design / History / 20th century / Exhibitions; Fashion design / History / 21st century / Exhibitions; Fashion / France / History / 21st century / Exhibitions; Chanel, Coco / 1883-1971; Chanel (Firm); Fashion; Fashion design; France; 1900-2099; exhibition catalogs; Exhibition catalogs; History; Catalogues d'exposition; Ausstellungskatalog